Muhadhoroh sebagai Training Public Speaking dalam Meningkatkan Self-Confidence Siswa - Ayunda Puspitasari; Muslimah Muslimah; Saiful Lutfi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Self-confidence is something that cannot be doubted because it is important for a person, with self-confidence one will feel comfortable with one's abilities, which can be seen from a high level of courage, social skills, responsibility and self-esteem. One way to increase self-confidence is through extracurricular muhadhoroh. The aim of this research is to find out how the muhadhoroh and muhadhoroh training process increases students' self-confidence. This type of research is descriptive qualitative, the research subjects are 4 ustad/ustadzah supervisors, the research informants are 5 class VII students. Data collection techniques include observation, interviews and documentation. The data validation technique uses source triangulation. Data analysis techniques through data collection, data reduction, data presentation and drawing conclusions. The results of this research show that the muhadhoroh training process includes script creation, manuscript collection, manuscript proofreading, and speech practice training (training in mastering the material, eliminating nervousness, clear word pronunciation, and use of body language). The public speaking training has produced a significant impact on students at SMPIT Hasanka Palangka Raya, such as being able to be calm when speaking in public, being able to control the audience and being brave in expressing their opinions.